Identification of the Marriage Delay Phenomenon in Girls: A Grounded Theory - mokhtari , samane; yosefi, zahra; Manshaee, Gholamreza (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to identify the marriage delay phenomenon in girls. Method: The research was qualitative and had a grounded theory and its statistical population consisted of single women over 30 years and its sampling was theoretical. 23 participants were female and the research tool was a semi-structured interview. The data analysis was based on Charms constructivist method (2006) and the final research model was presented at the end of the encoding process. Results: The results indicated that the causes of marriage delay were as follows: having an anti-marriage family, an individualistic personality, and living in a society that encourages celibacy. These factors were created due to three processes: Misconceptions about marriage, the facilitating characteristics of celibacy, and communicating with people who undermine matrimonialism. The marriage delay has led to effects, including negative emotional experiences, success in various dimensions, and dissatisfaction with the status quo. Eventually, single girls coped with the delay, both internally and externally. Conclusion: According to the findings, the marriage delay phenomenon occurred under certain causes and processes and had annoying consequences; hence, it required changes in the organization of social and family patterns and personality. The present study can be used by counselors and psychologists to develop and design content according to the values of society and its problems in this field.